Comparison of lauric acid and 12-hydroxylauric acid in the alleviation of drought stress in peach (Prunus persica (L.) Batsch) - Zhang, Binbin; Du, Hao; Sun, Maoxiang; Wu, Xuelian; Li, Yanyan; Wang, Zhe; Xiao, Yuansong; Peng, Futian (Frontiers in Plant Science, 2022)
Water shortage is one of the most important factors restricting the growth of peach trees. Plants produce fatty acids and their derivatives-Lauric acid (LA) and 12-Hydroxylauric acid (LA-OH), which are involved in abiotic stress responses, but the underlying mechanisms remain unclear. In this study, physiological examination revealed that 50ppm LA-OH and LA pretreatment reduced drought stress in P. persica, efficiently maintained leaf relative water content, and controlled relative conductivity increase. Under drought stress, LA-OH and LA treatments prevented the degradation of photosynthetic pigments, increase the degree of stomatal opening of leaves and enhanced the net photosynthetic rate. The reduction of the initial fluorescence value (F0), maximum fluorescence value (Fm), maximum quantum yield of PSII (Fv/Fm), real photochemical efficiency of ΦPSII (ΦPSII), and photochemical quenching coefficient (qP) of peach seedlings under drought treatment also significantly alleviated. In addition, the contents of MDA, O2- and H2O2 increased under drought stress, but LA-OH and LA treatments reduced the production of MDA and reactive oxygen species, and simultaneously increased the activities of SDO, POD, and CAT under drought stress. The results also showed that external Source LA-OH and LA treatments promoted the accumulation of solutes under stress and maintained the osmotic balance of cells by increasing the content of soluble sugars and proteins, proline and free amino acids. These results indicated that exogenous LA-OH and LA could alleviate the negative effects of drought stress and alleviate the damage caused by drought to peach seedlings. In conclusion, exogenous LA-OH and LA can alleviate the damage of peach seedlings caused by drought stress by enhancing the photosynthetic capacity and antioxidant capacity of peach seedlings, increasing the activities of protective enzymes and regulating the content of osmotic regulators. The application of exogenous LA-OH and LA can effectively reduce the drought stress of peach seedlings, which is worthy of further molecular mechanism exploration.